Micro and nanocomposites of polybutadienebased polyurethane liners with mineral fillers and nanoclay: thermal and mechanical properties - Ross, P. (2017)
Fil: Ross, Pablo. Instituto de Investigaciones Científicas y Técnicas para la Defensa (CITEDEF); Argentina